Association of Zinc Deficiency with Mortality in Preterm Neonates - Latif, Sameea; Hamid, Muhammad Haroon; Anjum, Ayesha; Tehreem, Shabana (Biological and Clinical Sciences Research Journal, 2025)
The role of trace elements, particularly zinc, in neonatal survival has received growing attention. Zinc is vital for immune function, cellular repair, and enzymatic activity. Preterm neonates are at risk of zinc deficiency due to insufficient intrauterine accumulation, which may influence morbidity and mortality outcomes. Objectives: To assess the association between zinc deficiency and mortality in preterm neonates. Methods: This was a cross-sectional study conducted at the Department of Pediatrics, Mayo Hospital, Lahore, from January 2024 to June 2024. A total of 130 preterm neonates (gestational age < 37 weeks) were enrolled. Serum zinc levels were measured once within 10 days of life using atomic absorption spectrophotometry. Zinc deficiency was defined as serum levels < 60 µg/dL. Neonates were categorized based on survival outcome (survived vs. expired), and zinc status was compared between groups. All neonates received standard NICU care. Data were analyzed using SPSS version 25, and the Chi-square test was applied to determine statistical significance. Results: Of the 130 neonates, 84 (64.6%) survived and 46 (35.4%) expired. Mean zinc level in the survived group was 84.2 ± 9.5 µg/dL and in the expired group was 82.6 ± 10.1 µg/dL. The association between zinc deficiency and mortality was statistically insignificant (p = 0.452). Conclusion: Zinc deficiency was not significantly associated with mortality in preterm neonates. Mortality is likely influenced by multifactorial causes beyond trace element status.